(untitled) (Khairulummah, 2024)
A Detailed Shariah Analysis of Diplomatic and Political Treaties between the Umayyad Caliphate and Non-Muslim States explores the intricate relationships forged between the Umayyad Caliphate and various non-Muslim entities during its expansive rule from 661 to 750 CE and this period, marked by significant territorial growth and cultural development, necessitated a sophisticated diplomatic approach to navigate interactions with Byzantine, Persian, and local tribes. As the first prominent Islamic dynasty, the Umayyads set critical precedents in diplomacy, blending military strategy with political negotiation in a diverse geopolitical landscape that included Islamic and non-Islamic societies. These diplomatic treaties are analyzed within the context of Shariah principles that governed relations between the Umayyads and their non-Muslim counterparts. Islamic teachings, emphasizing respect for envoys and the necessity of protecting diplomatic representatives, provided a foundational legal and ethical framework for treaty-making. Noteworthy examples include the Treaty of Hudaibiya and the Pact of ’Umar, which reflect a blend of strategic interests and adherence to Islamic law and the complex conditions that arose from these agreements. Implementing principles such as envoy impunity and the humanistic obligations of Muslim rulers highlights the dual role of diplomacy as both a tool for governance and a mechanism for promoting peace. Despite their diplomatic successes, the Umayyad Caliphate’s engagements were not without controversy. Scholarly debates have emerged over the authenticity and motivations behind certain treaties, with critiques focusing on religious rhetoric’s political appropriation and socio-political emotions’ influence during this tumultuous era. The interplay between military actions and diplomatic negotiations, especially in the context of internal dissent and the threat from rival powers, complicates understanding these treaties and their implications for later Islamic states. In sum, this analysis offers a comprehensive examination of the diplomatic strategies employed by the Umayyad Caliphate, illustrating their lasting impact on subsequent Islamic diplomacy and the intricate balance between governance, religious obligations, and the pragmatism required in statecraft. By elucidating the principles and controversies surrounding these treaties, the work contributes to a broader understanding of the dynamics between the Umayyad Caliphate and non-Muslim states and the enduring legacy of Islamic diplomatic practices.